2017
DOI: 10.1101/gad.289728.116
|View full text |Cite
|
Sign up to set email alerts
|

The PIDDosome activates p53 in response to supernumerary centrosomes

Abstract: Centrosomes, the main microtubule-organizing centers in animal cells, are replicated exactly once during the cell division cycle to form the poles of the mitotic spindle. Supernumerary centrosomes can lead to aberrant cell division and have been causally linked to chromosomal instability and cancer. Here, we report that an increase in the number of mature centrosomes, generated by disrupting cytokinesis or forcing centrosome overduplication, triggers the activation of the PIDDosome multiprotein complex, leadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
264
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(281 citation statements)
references
References 59 publications
17
264
0
Order By: Relevance
“…14 Fava and colleagues analyzed the cellular response to ploidy changes uncovering a similar surveillance mechanism relying on CASP2 and executed by p53. 15 Fava et al found that cells undergoing whole-genome duplication via cytokinesis failure were arrested in their proliferation by a process that involved the p53-independent activation of CASP2 by the PIDDosome. Activated CASP2 then promoted the stabilization of p53 via MDM2 cleavage, which resulted in p53 accumulation, cyclindependent kinase inhibitor 1A (CDKN1A, best known as p21) activation and cell cycle blockade (Fig.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…14 Fava and colleagues analyzed the cellular response to ploidy changes uncovering a similar surveillance mechanism relying on CASP2 and executed by p53. 15 Fava et al found that cells undergoing whole-genome duplication via cytokinesis failure were arrested in their proliferation by a process that involved the p53-independent activation of CASP2 by the PIDDosome. Activated CASP2 then promoted the stabilization of p53 via MDM2 cleavage, which resulted in p53 accumulation, cyclindependent kinase inhibitor 1A (CDKN1A, best known as p21) activation and cell cycle blockade (Fig.…”
mentioning
confidence: 99%
“…13 Three recent studies shed light on the mechanism of, and the signal responsible for, CASP2 activation during mitotic catastrophe unveiling the existence of a tight connection between CASP2 and the p53 pathway. [14][15][16] By analyzing colorectal cancers and cell lines displaying high levels of CIN, either at the baseline or upon the pharmacological abrogation of the SAC or increase of replication stress, Lopez-Garcia and colleagues identified a novel mechanism of tolerance to non-diploidy based on the downregulation of CASP2 expression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that centrosomal abnormalities may be sufficient to drive tumorigenesis in multiple tissues (16). The presence of extra centrosomes has been found to activate the p53-induced protein with a death domain (PIDDosome), a multiprotein complex, leading to caspase-2-mediated cleavage of murine double minute-2 (MDM2) and p53 accumulation (16).…”
Section: Centrosomal Amplificationmentioning
confidence: 99%
“…Indeed, a recent publication from Villunger and colleagues shows that PIDD is required to protect from aneuploidy. 5 Given that NPM1 has a proven role in regulating centriole duplication, it is possible that this function and other non-apoptotic functions attributed to caspase-2 are directed from the nucleolus. Consistent with this idea, we showed that blocking NPM1 increased cellular proliferation in a caspase-2 dependent manner.…”
mentioning
confidence: 99%